Impact of Optimizer Algorithm on NasNetMobile Model for Eight-class Retinal Disease Classification from OCT Images - Madhumithaa Selvarajan; Masoodhu Banu N. M (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA, 2026)
Artificial intelligence (AI) is an emerging technology that plays a vital role in various fields, including the medical field. Ophthalmology is the earliest field to adopt AI for diagnosing several retinal diseases. Many imaging techniques are available, but Optical Coherence Tomography (OCT) is particularly useful for early-stage diagnosis. OCT is a non-invasive imaging method that offers high-resolution visualization of the retinal structure, aiding the ophthalmologist in differentiating between normal and abnormal retina. Automated OCT-based retinal disease classification using deep learning (DL) is important for early disease detection. Most DL models achieved high performance, but the influence of the optimizer on model behaviour, convergence, and explainability remains a challenge. To bridge the gap, this study evaluates the performance and convergence of five optimizers, such as RMSprop, AdamW, Adam, Nadam, and SGD, on the NasNetMobile model. The model was trained on the OCT-8 dataset, which comprises seven diseased retinal classes and one normal class of Optical Coherence Tomography (OCT) images. The seven diseases are Age-related Macular Degeneration (AMD), choroidal neovascularization (CNV), Central Serous retinopathy (CSR), diabetic macular edema (DME), diabetic retinopathy (DR), DRUSEN, and Macular Hole (MH). The study also analyzes convergence behaviour and explainability through early stopping regularization technique and GradCAM XAI, respectively. The model achieved 71%, 93%, 96%, 97%, and 97% of accuracy, respectively. Compared with other optimizers, the SGD optimizer achieved high accuracy in 22 epochs, which indicates better generalization. GradCAM XAI highlights the disease-relevant region across different retinal diseases. This framework emphasizes the significance of selecting an appropriate optimizer for robust retinal disease classification using a DL model trained on OCT images